The Antioxidant Activities, Phenolic Total and Cytotoxicity of Extract and Fractions of Aloe Vera Linn) - Prahesti, Nike Rizky; Suzery, Meiny; Cahyono, Bambang (JURNAL SAINS DAN MATEMATIKA, 2015)
Aloe vera is known containing compounds which have potencies as antioxidants, such as group of anthraquinones (especially emodin and aloin), flavonoids, tannins, saponins, and sterols. In this research, comparison of total phenolics content, antioxidant activity and cytotoxicity of the methanolic extract and its fractions had been conducted. The Aloe vera extract was fractionated using a solvent gradient system to obtain fractions of n-hexane, dichloromethane, ethyl acetate and water. The analysis of total phenolic and activity were performed on extracts or fractions that showed a positive result to the phenolic test. Total phenolic content was determined by the Folin - Ciocalteu method, determination of antioxidant activity was by DPPH radical reduction and determination of cytotoxicity was by BSLT (Brine Shrimp Lethality Test). The results showed that the yield of methanol extract, fractions n-hexane, fraction of dichloromethane, ethyl acetate and water fraction were 0.580% ; 0.006% ; 0.093% ; 0.0092% and 0.410% respectively. Methanolic extract, ethyl acetate fraction and the water fraction showed positive result on phenolic test. Total phenolic compounds from water fractions was (16. mg gallic acid equivalent/g extract or fraction) which had greater level than Emet and Fea (12.47 and 0.89). Fraction of water had the highest antioxidant activity (IC50 433 mg/L) compared to Emet (IC50 519.23 mg/L) and Fea (IC50 1311.36 mg/L). All of three samples had cytotoxic potency, water fraction (Fair) was the most active sample (LC50 5.209 ppm) compared to Emet (LC50 18.383 ppm) and Fea (LC50 56.486 ppm). Overall it can be proposed that the water fraction is the most active fraction compared to the other fractions or extracts.